Peran Pola Asuh terhadap Penggunaan Gadget pada Anak Usia 10 Tahun di RW 02 Desa Mlekang - Mustikowati, Diyah; Setiawan, Deka; Masfuah, Siti (Didaktika, 2021)
This research investigated the role of parenting to the use of gadgets for children aged 10 years in hamlet 02 of Mlekang Village. Based on the results of interviews by the head of hamlet 02 of Mlekang Village, it was found that the results of data on parents of children aged 10 years on average work as traders, farmers and factory workers. This would be research material on how the form of parenting is seen from different family backgrounds. The researcher purpose to analyze the role of parenting applied by parents to the use of gadgets in children in hamlet 02 of Mlekang Village. The researcher used a qualitative descriptive method. This research was carried out in Mlekang Village, Gajah District, Demak Regency, by taking the subject of 10 students' parents and 10 children as research subjects consisting of 4 boys and 6 girls. This research used data collection techniques including the stages of observation, in-depth interviews, documentation, and recording. The data were analyzed using data reduction, data presentation, and drawing concluding. The results of the research showed that in providing a form of parenting students hamlet 02 of Mlekang Village used a form of democratic parenting. The form of democratic parenting has a positive impact on the use of students’ gadgets such as knowledge, expands friendship networks, and facilitates communication. There was also a suggestion in this study that parents are expected to be able to assist and share sufficient time with their students and parents should provide good parenting for their children because they can provide good role models.